EUCAST Testing of Isavuconazole Susceptibility in Aspergillus: Comparison of Results for Inoculum Standardization Using Conidium Counting versus Optical Density - Arendrup, Maiken Cavling (Antimicrob Agents Chemother, 2014)
The EUCAST E.DEF9.1 standard recommends standardization of the inoculum concentration by conidium counting using a hemocytometer rather than a spectrophotometer. In this study, we investigated whether the choice of these methods influenced isavuconazole MICs. A blinded collection of 30 molecularly characterized azole-resistant isolates and 10 wild-type Aspergillus fumigatus isolates was shared with four different laboratories. Additionally, each laboratory selected approximately 100 A. fumigatus isolates and 50 isolates each of A. flavus, A. nidulans, A. niger, and A. terreus (1,237 isolates in total). Three laboratories (laboratories 1 to 3) used conidium counting. One laboratory standardized the inoculum using a spectrophotometer (that is, by use of the optical density [OD]) and is referred to as the OD laboratory. Correlation coefficients, intraclass correlation coefficients, and essential agreement were calculated, and 2-log-unit differences were assessed (paired t test). The MIC range for the blinded collection was 0.25 to 16 mg/liter, and a 1-dilution-step difference between the MIC(50) and MIC(90) across the four laboratories was detected and a 2-dilution-step difference between the modal MICs was detected. Compared to the results for laboratories 1 and 2, a significant correlation was found for the OD laboratory MIC data (correlation coefficients, 0.85 and 0.93, respectively; intraclass correlation coefficients, 0.88 and 0.96, respectively). The number of mutant isolates whose MICs overlapped those of the wild-type isolates was the lowest for the OD laboratory (14/30 [46.7%] mutant isolates), whereas the numbers were 18/30 (60%) isolates for laboratory 1, 17/30 (56.7%) isolates for laboratory 2, and 21/30 (70%) isolates for laboratory 3. For the A. flavus, A. fumigatus, A. nidulans, A. niger, and A. terreus isolates, comparative analysis again defined the MIC distributions from the OD laboratory to be in excellent agreement with those from laboratories 1 and 2 across all five Aspergillus spp. The findings suggest that EUCAST testing using OD determination is an appropriate alternative for standardization of Aspergillus inoculum concentrations.